Brain Targeted Delivery of Curcumin Using P80-PEG-Coated Poly(lactide-co-glycolide) Nanoparticles - K. Das1, Malay; Husain3, Kazim; Pathak1, Yashwant (Asian Journal of Chemistry, 2013)
The low density lipoprotein (LDL) receptor has been shown to be upregulated in gliblastomamultiforme (GBM) tumor cells and is therefore a potential molecular target for the delivery of therapeutic agents. We prepared poly(lactide-co-glycolide) (PLGA) nanoparticles incorporating curcumin by nanoprecipitation technique with ultrasonication. The nanoparticles were found to be below 100 nm suitable for passive brain targeting to low density lipoprotein receptors overexpressed in gliblastomamultiforme tumor cells. The in vitro drug release study showed sustained drug delivery for 2 days with no initial burst release. The antitumor activity of the optimized nanoformulation was investigated in vitro by tumor cell uptake of curcumin loaded nanoparticles and further confirmed by cytotoxicity of U87MG brain tumor cells. The nanoparticles showed the higher cytotoxicity over pure drug due to their efficient internalization into the tumor cells. The surface coating with polysorbate 80 (P80) and poly(ethylene glycol) (PEG) showed the best antitumor activity. The results suggest that the poly(lactide-co-glycolide) nanoparticles incorporating curcumin had antitumor activity and are the promising system for brain tumor targeted drug delivery.